Доклад Юнэйдс О Глобальной Эпидемии Спида 2022 - UNAIDS (United Nations, 2022)
New data from UNAIDS on the global HIV response reveals that during the last two years of COVID-19 and other global crises, progress against the HIV pandemic has faltered, resources have shrunk, and millions of lives are at risk as a result. The new report, In Danger, is being launched ahead of the International AIDS Conference in Montreal, Canada.